2010
DOI: 10.1177/0095327x10390463
|View full text |Cite|
|
Sign up to set email alerts
|

The World War II Veteran Advantage? A Lifetime Cross-Sectional Study of Social Status Attainment

Abstract: The impact of military service on the social status attainment of World War II veterans has been studied since the 1950s; however, the research has failed to come to any consensus with regard to the level of their attainment. Analyses have generally focused on cross-sectional data or longitudinal data without considering the effects of military service over the life course. In this study I argue that World War II veterans had greater social attainment over their lifetimes; that black World War II veterans atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…According to later work, World War II veterans did earn a premium relative to nonveterans in simple regressions (Angrist and Krueger 1994;Small and Rosenbaum 2008;Teachman and Tedrow 2004). They had higher income and prestige than comparable nonveterans (Smith et al 2012). Yet in regressions that include instrumental variables, veterans either did not differ from nonveterans or earned less, suggesting that the apparent positive association is explained not by employers' choices but by selection into the armed forces (Angrist and Krueger 1994;Small and Rosenbaum 2008).…”
Section: How Cohorts Differmentioning
confidence: 97%
“…According to later work, World War II veterans did earn a premium relative to nonveterans in simple regressions (Angrist and Krueger 1994;Small and Rosenbaum 2008;Teachman and Tedrow 2004). They had higher income and prestige than comparable nonveterans (Smith et al 2012). Yet in regressions that include instrumental variables, veterans either did not differ from nonveterans or earned less, suggesting that the apparent positive association is explained not by employers' choices but by selection into the armed forces (Angrist and Krueger 1994;Small and Rosenbaum 2008).…”
Section: How Cohorts Differmentioning
confidence: 97%
“…As mentioned earlier, there is controversy about the effect of military experience on earnings. Scholars found that military service during World War II boosted the income of U.S. veterans (e.g., Angrist & Krueger, 1994; De Tray, 1982; MacLean & Kleykamp, 2021; Smith et al, 2012), while Vietnam-era veterans earned less (e.g., Angrist, 1990; Spiro et al, 2016; Teachman & Call, 1996). Even so, most of prior studies affirmed the positive effects of military service on the earnings of some socially disadvantaged groups, such as minorities, rural people, and women (Angrist, 1998; Hou et al, 2020; Padavic & Prokos, 2017; Sheehan & Hayward, 2019), because military service tends to help them gain access to elite jobs and narrow gaps in human and social capital.…”
Section: Theoretical Hypothesesmentioning
confidence: 99%
“…As a special experience in the life course, military service had a pervasive and profound impact on men’s socioeconomic status and health outcomes (Angrist, 1990; Fredland & Little, 1985; Kleykamp, 2009; Smith et al, 2012; Zhao & Guo, 2022). While extensive literature assessed the health effects of military service in developed countries (e.g., Angrist et al, 2010; Bedard & Deschênes, 2006; Dobkin & Shabani, 2009; Johnston et al, 2016), few investigated the health status of elderly veterans in the context of developing countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Related, some research finds that veterans are advantaged in some ways upon reentering civilian life, at least initially (e.g., Smith et al, 2012, on World War II veterans). There seems, then, to be some connection here, with Union veterans and their pensions aiding the development of postwar civil society. …”
mentioning
confidence: 99%